Mutation spectrum of PTS gene in patients with tetrahydrobiopterin deficiency from jiangxi province - Xie, Kang; Zeng, Baitao; Zhang, Liuyang; Chen, Shaohong; Zou, Yongyi; Yuan, Huizhen; Huang, Shuhui; Wang, Feng; Lu, Qing; Liu, Yanqiu; Yang, Bicheng (Frontiers in Genetics, 2022)
Background: Hyperphenylalaninemia (HPA) is the most common inborn error in amino acid metabolism. It can be primarily classified into phenylalanine hydroxylase (PAH) deficiency and tetrahydrobiopterin (BH4) deficiency. BH4 deficiency (BH4D) is caused by genetic defects in enzymes involved in the biosynthesis and regeneration of BH4. 6-pyruvoyl-tetrahydropterin synthase (PTPS/PTS), which is encoded by the PTS gene, participates in the biosynthesis of BH4. PTPS deficiency (PTPSD) is the major cause of BH4D. In this study, we investigated that the prevalence of BH4D in Jiangxi province was approximately 12.5 per 1,000,000 live births (69/5,541,627). Furthermore, the frequency of BH4D was estimated to be 28.8% (69/240) in the HPA population of Jiangxi. In this study, we aimed to characterize the mutational spectrum of the PTS gene in patients with PTPSD from Jiangxi province. Method: Newborn screening data of Jiangxi province from 1997 to 2021 were analyzed and 53 families with PTPSD were enrolled for the analysis of the PTS gene variants by Sanger sequencing. Results: 106 variants were identified in 106 alleles of 53 patients with PTPSD, including 13 types of variants reported previously, and two novel variants (c.164-36A>G and c.146_147insTG). The predominant variant was c.259C>T (47.2%), followed by c.84-291A>G (19.8%), c.155A>G (8.5%), c.286G>A (6.6%) and c.379C>T (4.7%). Conclusion: The results of this study can not only provide guidance for the molecular diagnosis and genetic counseling in cases of PTPS deficiency but also enrich the PTS mutation database.